Evaluasi Pengadaan Tanah Skala Kecil dengan dan tanpa Penetapan Lokasi di Kabupaten Sleman - Sari, Wenny Yolanda Ratna; Prasetyo, Priyo Katon; Sudibyanung , Sudibyanung (Sekolah Tinggi Pertanahan Nasional, 2021)
Land availability is the great significant part in infrastructure development. To support the land availability, the government pursues a program called land acquisition. Land acquisition is regulated in Law Number 2 of 2012 and Government Regulation Number 71 of 2012. Based on Government Regulation Number 40 of 2014, land acquisition is divided into two, including large scale with an area of more than 5 hectares and small scale based with an area of less than 5 hectares. Small-scale land acquisition is further regulated in Presidential Regulation Number 148 of 2015 Article 121 paragraph (3) which does not require a determination of location. The purpose of this study was to determine the implementation process as well as the advantages and disadvantages of small-scale land acquisition with and without location determination in Sleman Regency. This research used a qualitative method with a descriptive approach. The results of this research showed that the implementation of land acquisition with determination of location has advantages (4) and weaknesses (6) while land acquisition without determination of location has advantages (6) and disadvantages (4).